PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (Studi pada siswa kelas V SD Islam Terpadu Madani Kabupaten Aceh Tenggara - Harudin, Mardianto, Edi Saputra (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2018)
Abstract: This study was intended 1) To find out the learning activities of students before applying theapproach to Contextual Teaching and Learning (CTL) on Islamic Education of five graders at MadaniIslamic Integrated Elementary school. 2) To find out the learning activities of students after the applicationof the Contextual approach to Teaching and Learning (CTL) on Islamic Education of five graders atMadani Islamic Integrated Elementary school. 3) To find out if there is an increase in students after learningactivities implemented Contextual Teaching and Learning (CTL) and learning local wisdom on IslamicEducation of five graders at Madani Islamic Integrated Elementary school. The results showed that theapplication of CTL approach in local wisdom-based learning can improve student learning activities onislamic Education subject. Islamic Education Subject learning activities was increased from cycle I thenincreased in cycle II.Penelitian ini bertujuan untuk (1) Untuk mengetahui aktivitas belajar siswa sebelum penerapan pendekatanContextual Teaching and Learning (CTL) pada mata pelajaran PAI kelas V di SD Islam Terpadu Madani.(2) Untuk mengetahui aktivitas belajar siswa setelah penerapan pendekatanContextual Teaching andLearning (CTL) pada mata pelajaran PAI kelas V di SD Islam Terpadu Madani. (3) Untuk mengetahuiapakah terdapat peningkatan aktivitas belajar siswa setelah diterapkanContextual Teaching and Learning(CTL) dan pembelajaran kearifan lokal pada mata pelajaran PAI kelas V di SD Islam Terpadu Madani.Hasil penelitian menunjukkan penerapan pendekatanCTL dalam pembelajaran berbasis kearifan lokalmampu meningkatkan aktivitas belajar siswa pada mata pelajaran PAI. Aktivitas belajar PAI mengalamipeningkatan dari siklus I kemudian meningkat pada siklus II.Kata Kunci: Pendekatan CTL, Kearifan Lokal dan Aktivitas Belajar